PENGEMBANGAN BUKU AJAR BERMUATAN NILAI-NILAI KARAKTER PADA MATERI USAHA DAN MOMENTUM UNTUK PEMBELAJARAN FISIKA SISWA KELAS XI SMA - Mila Anggela (PILLAR OF PHYSICS EDUCATION, 2013)
Abstract The research is development research that perpose for: 1) Understanding validity of learning book that contain the character values in material of work and momentum for physics learning class XI senior high school. 2) describing the making of result learning book that contain the character values in material of work and momentum for physics learning class XI senior high school. 3) Understanding practically and evectivitity of learning book that contain the character values in material of work and momentum for physics learning class XI senior high school. This learning book was developed use research and development metod. As object of research was learning book that contain character value for class XI first semester senior high school in material of work and momentum and subject of try out was student in class XI science 3 SMAN 1 Batang Anai. The result of this research: first learning book that contain character values is very valid with average velue is 92,05. Second, desain of this learning book such as: cover, main page, learning guidelines, concept map, standar competence, content of learning material, supporting information, examples exercisesm worksheet, homework, evaluation, key answer, feedback and reference. Third, the result of practically is very practice with average value, is 92,88 for teachers conception and 91,13 for students conception. The result of efectivity in cognitive domain have increace 21,75, average in effective domain is 89,11 and average in psychomotor domain was 89,13.   Keywords: character values, learning book, work and momentum